Penerapan Metode EOQ (Economic Order Quantity) dalam Pengendalian Persediaan Bahan Baku - Sandra Ayu A; Kokom Komariah; Faizal Mulia Z (Journal of Management and Bussines (JOMB), 2022)
The purpose of this study was to analyze raw material inventory control with the Economic Order Quantity (EOQ) method on CV. BJT with 47 Embroidery Sukabumi City. The research method used is descriptive quantitative to describe and describe the data. The data is processed using the EOQ method using the EOQ method to determine the total cost of inventory. The results show that there is a large difference if using the EOQ method, the savings are more efficient. The conclusion is that by applying the EOQ method, we can optimize raw material inventory by minimizing raw materials with increased inventory. Keywords: Economic Order Quantity (EOQ), Raw Material Inventory